Fault detection and analysis of Kapton film in fuel cells using image processing - Firdous, R.; Aherrao, S.; Narute, B.; Borkar, V. (International Conference on Computing, Analytics and Security Trends, CAST 2016, 2017)
Fuel cell is one of the best alternatives of fossil energy in the modern scenario. But still there are some shortcomings such as durability and reliability, which block the wide application of fuel cells. To overcome these barriers, fault diagnosis is an efficient solution. This paper proposes a method for finding dimensional accuracies in Kapton films in membrane electrode assemblies (MEA) of fuel cells using image processing tools for offline fault analysis. © 2016 IEEE.
Keywords: Dimensional accuracy; Fault analysis; fault detection; Fossil energy; fuel cell; Gas fuel purification; image analysis; Image processing; Image processing tools; Kapton films; Membrane electrode assemblies; Offline; polyimides